2016
DOI: 10.3892/ol.2016.4369
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of pregnane X receptor and ATP-binding cassette sub-family B member 1 in peripheral blood: A prospective indicator for drug resistance prediction in non-small cell lung cancer

Abstract: The aim of the present study was to investigate the protein expression profiling of pregnane X receptor (PXR) and ATP-binding cassette sub-family B member 1 (ABCB1; also known as MDR1 or P-gp), present in the peripheral blood mononuclear cells (PBMCs) and cancerous tissues of cases of non-small cell lung cancer (NSCLC). Furthermore, the study aimed to assess the feasibility of predicting drug resistance through the medium of PBMCs. Of the subjects included in the study, 37 were histopathologically diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…In the current study, we observed a decrease in methylation following the MBC2 intervention, which may indicate an upregulation of DUSP5P1 and tumor suppression. Kong et al found that, among non-small cell lung cancer cases (n = 37) compared to controls (n = 17), NR1I2 (aka PXR) expression was significantly higher among non-small cell lung cancer tumors compared to peripheral blood mononuclear cells [47]. We also observed that methylation increased in this region following MBC2, which may indicate that a healthier lifestyle downregulates the protein in immune cells.…”
Section: Discussionsupporting
confidence: 53%
“…In the current study, we observed a decrease in methylation following the MBC2 intervention, which may indicate an upregulation of DUSP5P1 and tumor suppression. Kong et al found that, among non-small cell lung cancer cases (n = 37) compared to controls (n = 17), NR1I2 (aka PXR) expression was significantly higher among non-small cell lung cancer tumors compared to peripheral blood mononuclear cells [47]. We also observed that methylation increased in this region following MBC2, which may indicate that a healthier lifestyle downregulates the protein in immune cells.…”
Section: Discussionsupporting
confidence: 53%
“…Likewise, in previous studies, compared with normal tissues like bronchial epithelium and alveolar tissues in the normal lung, the neoplastic tissues such as NSCLC cells expressed the PXR at a significantly higher level, which suggested that PXR selectively participated in the development of tumorigenesis . Furthermore, PXR participates in resistance to chemotherapeutics by regulating the expression of some enzymes or transports that are associated with the metabolism of the drug . Therefore, PXR can be used to predict the potential risk of drug resistance in NSCLC patients.…”
Section: Discussionmentioning
confidence: 88%
“…The collected cells were centrifuged and the supernatant was extracted by ethyl acetate. The freeze drying powders were then dissolved in 200 μL methyl alcohol/water solutions (65: 35, v/v). Taxol and 6′-hydroxyl Taxol were analyzed by high-performance liquid chromatography (HPLC) assay (injection volume: 20 μL, analytical column: C18, eluent: methyl alcohol/water (65:35, v/v), flow rate: 1 mL/min).…”
Section: High-performance Liquid Chromatographymentioning
confidence: 99%
“…Like colon carcinogenesis, a PXR polymorphism in the 3′ UTR predicts for low PXR levels and increased lung cancer risk in smokers from China (Zhang et al, 2014a). Very recently, PXR was proposed to be a novel biomarker for predicting drug resistance in non-small cell lung cancer patients (Kong et al, 2016). …”
Section: Differential Role Of Pxr In Cancermentioning
confidence: 99%